Nghiên cứu ảnh hưởng của tỷ lệ các hợp phần đến phản ứng khâu mạch nhựa epoxy biến tính dầu ve bằng polyisoxyanat - Thành, Đỗ Minh; Hiền, Lê Xuân; Dũng, Nguyễn Tiến (Vietnam Journal of Chemistry, 2016)
The influence of the contents of epoxy resin modified by castor oil (ECO), polyisocyanate (PI) on the crosslinking reaction of ECO by PI at 155 oC have been studied. It was shown that the increase of PI content in the curing systems from 20 to 60 % led to decrease of the rate of the consumtion of isocyanate, hydroxyl and epoxy groups and corresponding change of amide groups, resulted in considerable improvement of the relative hardness and gloss of the cured coatings. The weight ratio of EDV/PI = 50/50 have been determined to be optimal condition for formation of the cured coating having gel fraction, swelling degree, flexibility, adhesion, impact resistance, gloss at 60o and relative hardness of 98 %; 126 %; 1 mm, 1 point, 200 kG.cm, 95 % and 0.97, respectively. Keywords. Epoxy resin, castor oil, polyisoxyanate, curing